PEMANFAATAN LIMBAH AYAM POTONG MENJADI PUPUK ORGANIK BERKUALITAS DAN BERNILAI EKONOMIS DI DESA KARANGAN, KECAMATAN BARENG, KABUPATEN JOMBANG - Purnomo Edi Sasongko; Purwadi, Purwadi; Hidayat, Ramdan (Universitas Mataram, 2024)
Geographically, the Bareng District area, Jombang Regency is located at 50 East Longitude and 70 South Latitude with an area of more than 6,422 ha with 3,192 ha of rice fields, 2,243 ha of dry land and 237 ha of community forest with great potential for the development of agricultural industries based on food and horticultural commodities. The livelihoods of the people of Karangan Village largely rely on produce from gardens and agricultural labor. There are several chicken cages in the Bareng District area with a volume of chicken manure waste of approximately 6 tons per day. On the other hand, chicken manure waste can be recycled as manure and charcoal products as well as chicken manure waste ash which have sales value and have the potential to be managed in small and medium scale enterprises (UKM)